Photochemical Oxidation of NIR Photosensitizers in the Presence of Radical Initiators and Their Prospective Use in Dental Applications. Issue 3 (21st March 2016) - Brömme, Thomas; Schmitz, Christian; Moszner, Norbert; Burtscher, Peter; Strehmel, Nadine; Strehmel, Bernd
Abstract: Photochemical oxidation of near infrared (NIR) photosensitizers in the presence of diaryl iodonium salts bearing either bis(trifluoromethylsulfonyl)imide or hexafluorophosphate was investigated by exposure with NIR LEDs emitting either at 790 nm, 830 nm, 850 nm or 870 nm. Four different cyanines with barbituryl group at the meso position exhibit similar absorption in the NIR. These photosensitizers initiate in combination with diaryliodonium salts radical photopolymerization of dental composites with the focus to cure large thicknesses. Furthermore, the mixture comprising the cyanine and the iodonium salt was used to generate brown color in dental composites on demand. This required to understand the mechanism of dye decomposition in more detail applying exposure kinetics and a coupling of Ultra Performance Liquid Chromatography (UPLC) with mass spectrometry (MS) to analyze the photoproducts formed. Data showed cleavage of the polymethine chain at typical positions in case of the oxidized species. These were formed as result of electron transfer between the excited state of the photosensitizer and the iodonium salt. UPLC‐MS experiments additionally indicated a certain sensitivity of the system upon adding of acids and radicals generated by thermal treatment of azobisisobutyronitrile (AIBN). Thus, treatment of the photoinitiator composition led almost to the same products no matter the system was either exposed with NIR light or treated with acids or radicals generated by thermal decomposition of AIBN. These findings helped to understand the large curing depth of 14 mm upon NIR exposure at 850 nm and the brown color formed. Abstract : NIR‐sensitized photopolymerization opens the opportunity to cure samples with large thickness (>1 cm) using functionalized cyanines and iodonium salts. Addition of fillers reduces the curing length but the decrease is not as strong compared to a commercial visible operating bleaching photoinitiator system. Photoproducts formed depict a permanent stable brown color.